A review on health impacts, monitoring and mitigation strategies of arsenic compounds present in air - Vishwakarma Y.K.; Tiwari S.; Mohan D.; Singh R.S. (My University, 2025)
Arsenic, even in trace concentration presents several adverse impacts on human health and are classified among carcinogenic species. The subsequent health concerns owing to consumption of arsenic contaminated water has been widely reported, however, the presence and effects of arsenic through air still remains to be explored thoroughly, due to the availability of limited research and literature; the reason being difficulty in estimation of arsenic compounds in gaseous or particulate associated form. The objective of the current review is to present a detailed picture of sources, estimation techniques and control strategies available currently and propose futuristic approaches for abatement of the problem. A summary of the studies conducted globally has been included in the review with an objective to figure out the occurrence and exposure to arsenic in different parts of the world, exposure assessment and control strategies followed to overcome the problem. Studies on dispersion of As in gaseous or particulate form has also been discussed, on the basis of ground observation as well as predicted models. © 2021 The Authors